Effects of selected inherited factors on susceptibility to SARS-CoV-2 infection and COVID-19 progression - Hubacek, J A (Physiological research, 2021)
Genetic predispositions may influence geographical and interethnic differences in COVID-19 prevalence and mortality in affected populations. Of the many genes implicated in COVID-19 progression, a substantial number have no direct functional link on virus transfer/viability or on the host immune system. To address this knowledge deficit, a large number of in silico studies have recently been published. However, the results of these studies often contradict the findings of studies involving real patients. For example, the ACE2 has been shown to play an important role in regulating coronavirus entry into cells, but none of its variations have been directly associated with COVID-19 susceptibility or severity. Consistently was reported that increased risk of COVID-19 is associated with blood group A and with the APOE4 allele. Among other genes with potential impacts are the genes for CCR5, IL-10, CD14, TMPRSS2 and angiotensin-converting enzyme. Variants within the protein-coding genes OAS1 and LZTFL1 (transferred to the human genome from Neanderthals) are understood to be among the strongest predictors of disease severity. The intensive research efforts have helped to identify the genes and polymorphisms that contribute to SARS-CoV-2 infection and COVID-19 severity.
Keywords: Animals; genetická predispozice k nemoci; Host-Pathogen Interactions; Polymorphism, Genetic; progrese nemoci; Heredity; Risk Assessment; Serine Endopeptidases; rizikové faktory; Genetic Predisposition to Disease; Humans; ABO Blood-Group System; Apolipoproteins E; ABO systém krevních skupin; polymorfismus genetický; Phenotype; apolipoproteiny E; interakce hostitele a patogenu; lidé; serinové endopeptidasy; fenotyp; SARS-CoV-2; zvířata; angiotensin-konvertující enzym 2; Risk Factors; hodnocení rizik; Disease Progression; dědičnost; Angiotensin-Converting Enzyme 2; COVID-19